Impact of 5-azacytidine on rat decidual cell proliferation - Fabijanovic, Dora (BlackWell Publishing Ltd, 2014)
The DNA demethylating agent 5-azacytidine (5-azaC) has a teratogenic influence during rat development influencing both the embryo and the placenta. Our aim was to investigate its impact on early decidual cell proliferation before the formation of placenta. Thus, female Fischer rats received 5-azaC (5 mg/kg, i.p.) on the 2nd, 5th or 8th day of gestation and the decidual tissues were harvested on gestation day 9. They were then analysed immunohistochemically for expression of cell proliferation marker proliferating cell nuclear antigen (PCNA) in decidual cells and for global DNA methylation using the coupled restriction enzyme digestion, random amplification and pyrosequencing assays. We found that 5-azaC administered on the 5th and 8th (but not on 2nd) day of gestation led to increased PCNA expression in decidual cells compared with untreated controls. No significant changes in DNA methylation were detected, with either method, in any of the treated rat groups compared with untreated controls. Thus, we conclude that 5-azaC can stimulate decidual cell proliferation without simultaneously changing global DNA methylation level in treated cells.